PENGARUH KEPERCAYAAN DIRI TERHADAP KECEMASAN MAHASISWA YANG SEDANG MENYUSUN SKRIPSI - Simanullang, Antika (Dharmas Education Journal (DE_Journal), 2024)
This study aims to analyze the influence of self-confidence on the level of anxiety of students who are working on a thesis in the City of Medan, based on a study that has been conducted that the self-confidence categorization criteria are shown to have low self-confidence. categorization 113 people (63.8%), medium categorization 113 people 12 people (6.8%), high category 52 people (29.4%). And low level of anxiety is 110 people (65.8%), moderate categorization is 14 people (8.5%), high categorization is 53 people (30.5%). Self-confidence is considered to be an important factor that can influence students' level of anxiety in facing this academic challenge. The research method used is a quantitative approach with survey techniques. By using the SPSS application version 20 for Wimdows to reveal the results of the hypothesis using regression analysis techniques, there is a significant influence of 0.000 (sig<0.05). The value of the simple regression coefficient obtained from the study is 0.276 and the significance is 0.000, which shows that there is an influence of self-confidence on anxiety and the hypothesis in this study is accepted. This finding shows that increasing self-confidence can be one of the solutions to reduce the anxiety experienced by students when completing their thesis. Therefore, universities are advised to provide more intensive support in increasing students' self-confidence, through guidance and counseling programs.